2020
DOI: 10.31557/apjcp.2020.21.12.3509
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Smart Scope® Visual Screening Test with Naked Eye Visual Screening and Pap Test

Abstract: Background: Cervical cancer is a major contributor to mortality and morbidity in women. Naked eye visual screening (NE test) and Pap test are commonly used for cervical cancer screening. Both tests have inherent limitations like low sensitivity (Pap test) and subjectivity in interpretation, lack of permanent record and overestimation (NE test). Here, Smart Scope ® visual screening test (SS test) was compared with NE and Pap tests. Smart Scope ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…On histopathological examination we found that, 79.1% of the patients had benign in nature cervix and 20.9% had malignant in nature cervix. In agreement with our study, Rahatgaonkar et al (13) found that maximum; number of women, (300/509:58.9%), were reported to have normal cytology followed by 169 (33.2%) with inflammatory smears. They also demonstrated that on NE test, 141 were screen-positive (27.7%), and 367 were screennegative (72.1%), which is also in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…On histopathological examination we found that, 79.1% of the patients had benign in nature cervix and 20.9% had malignant in nature cervix. In agreement with our study, Rahatgaonkar et al (13) found that maximum; number of women, (300/509:58.9%), were reported to have normal cytology followed by 169 (33.2%) with inflammatory smears. They also demonstrated that on NE test, 141 were screen-positive (27.7%), and 367 were screennegative (72.1%), which is also in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The EVA® device was another unique device which was a custom adaptation to a Samsung® Galaxy smartphone housed in a case that features additional magnification, stabilizer, optics, and attachable stand. Although this device uses a standard smartphone as an integrated component, it closely resembles a colposcope in capability and is referred to as digital colposcopy in two studies ( Goldstein et al, 2020 , Peterson et al, 2016 , Thay et al, 2019 , Gabaza et al, 2019 , Gharabaghi et al, 2019 , Oyiengo et al, 2018 , Rahatgaonkar et al, 2020 , Singhakum et al, 2018 , Srinivas et al, 2021 , Medical doctors, 2021 , Asgary et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four other studies did not include any of the above devices: in a 2018 study by Singhakum et al, the custom device was described as “portable customized handheld digital cervicography camera,” but the article otherwise did not describe specifics ( Srinivas et al, 2021 ). In a 2019 study by Garabaghi et al, investigators described their device as a “specialized cervicography camera,” also did not include specifics ( Rahatgaonkar et al, 2020 ). Two other studies did not specify their method to obtaining cervical imaging ( Gharabaghi et al, 2019 , Rahatgaonkar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideology of smartscopy is that, instead of using an external flash and a device separately, the smartphones are used. This method is done after the application of a 3% solution of acetic acid to the cervix for 1 min, once the application is over a gynecologist inspects the cervix using Smartscopy with the activated flash mode pictures of the cervix ( 36 ). The recorded prominent areas revealed abnormal epithelium.…”
Section: Methodsmentioning
confidence: 99%